THE IMPORTANCE OF LICORICE IN OUR LIVES (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
Licorice is used in several industries. Licorice root also has several medicinal properties, it is used to treat almost all types of lung, liver, circulatory and kidney diseases. Licorice is also an ingredient in some topical (skin application) products. Certain products containing licorice root and other ingredients can help relieve indigestion. While licorice has a number of beneficial properties, it also has some of its own side effects. Licorice is thought to derive from a component called glycyrrhizic acid. that is, diomo may not have useful features. We will provide similar useful information in this article.